Infection-Related Stillbirths: A Detailed Examination of a Nine-Year Multidisciplinary Study - Liliana Gabrielli; Matteo Pavoni; Francesca Monari; Federico Baiesi Pillastrini; Maria Paola Bonasoni; Chiara Locatelli; Maria Bisulli; Alessandra Vancini; Ilaria Cataneo; Margherita Ortalli; Giulia Piccirilli; Alessia Cantiani; et al. (Microorganisms)
Background: Although several conditions and specific risk factors have been associated with stillbirth (SB), in most of the cases it is difficult to identify the definitive etiopathology and cause of death. Specifically, the role of infections in SB is still debated. Our aim was to study maternal, placental, and fetal tissues in cases of SB in order to define the causative link between infections and fetal death, through a multidisciplinary clinical audit. Methods: Between 2014 and 2022, microbiological investigations on maternal, placental and fetal samples of SB cases were performed according to a standardized protocol including serology, cultures, and molecular biology. Autopsies and placental examination were mandatory in all SB cases. Results: A total of 182 cases of SB were investigated. Bacteria were detected in 22.2% of vaginal swabs, 65% of placental biopsies, 29% of fetal blood, and 14.1% of oropharyngeal swabs. Vaginal and oropharyngeal swabs were positive for urogenital mycoplasmas in 25.2% and 8.6%, respectively. Positive results of microbiological investigations, in association with histological features suggestive of infection, were observed in six cases, indicating that fetal death was likely related to a bacterial infection. In one case, a high SARS-CoV-2 load was found in the placenta of a SB due to placental abruption. Conclusions: Infections were likely associated with fetal death in 3.8% of cases. Thus, in developed countries, an infection, defined when positive microbiological findings are associated with histological evidence of organ damage, is a minor contributory factor in SB.